2008
DOI: 10.1158/1078-0432.ccr-07-1517
|View full text |Cite
|
Sign up to set email alerts
|

N-[N-[(S)-1,3-Dicarboxypropyl]Carbamoyl]-4-[18F]Fluorobenzyl-l-Cysteine, [18F]DCFBC: A New Imaging Probe for Prostate Cancer

Abstract: Purpose: Previously, we showed successful imaging of xenografts that express the prostatespecific membrane antigen (PSMA) using small-animal positron emission tomography (PET) and the radiolabeled PSMA inhibitor]methyl-L-cysteine. Herein, we extend that work by preparing and testing a PSMA inhibitor of the same class labeled with fluorine-18. High radiopharmaceutical uptake was also seen in kidneys and bladder; however, washout of radioactivity from these organs was faster than from the PIP tumors. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
153
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 35 publications
2
153
0
2
Order By: Relevance
“…Since then many small molecular PSMA-targeting imaging agents have been developed for single-photon emission tomography (SPECT), PET, and optical imaging (2130). Among these imaging agents, the urea-based 18 F-DCFBC (25, 31, 32), 123 I-MIP-1072 (26), and 123 I-MIP-1095 (33) have entered into clinical trials and shown the ability to detect both bone and soft-tissue metastases in patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Since then many small molecular PSMA-targeting imaging agents have been developed for single-photon emission tomography (SPECT), PET, and optical imaging (2130). Among these imaging agents, the urea-based 18 F-DCFBC (25, 31, 32), 123 I-MIP-1072 (26), and 123 I-MIP-1095 (33) have entered into clinical trials and shown the ability to detect both bone and soft-tissue metastases in patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[21] To validate the in vivo imaging data, [ 111 In]1 was also assessed for its pharmacokinetics ex vivo. Table 1 [15] which has recently been administered to human subjects. PSMA specificity and selectivity of [ 111 In]1 was further confirmed by effective blocking in PSMA + PC3 PIP tumor and kidney ( Figure S9) using a dose 50 mg/Kg of the potent, selective…”
mentioning
confidence: 99%
“…For example, we recently tested the prostate-specific membrane antigen (PSMA) as an imaging reporter and showed it performed as well or better than HSV1-tk or hNIS for imaging of animal models of human cancer (Castanares et al, 2014). PSMA would be a good candidate for a theranostic reporter as many imaging and therapeutic probes have already been developed for this human protein (Banerjee et al, 2008; Chen et al, 2009, 2008; Foss et al, 2005; Hillier et al, 2009; Mease et al, 2008; Pomper et al, 2002; Shallal et al, 2014), including several radiolabeled molecules that are in clinical trials (Barrett et al, 2013; Cho et al, 2012; Hillier et al, 2011). …”
Section: Discussionmentioning
confidence: 99%